Golf Techniques - Lawrenson, Derek (London Chancellor Press, 2006)
This step-by-step guide includes practice drills and tips, warm-up exercises, stretches, rules, etiquette, troubleshooting and how to calculate a handicap.
Include Glossary, Index and Colored Illustrations.
Keywords: Golf -- Golf--Psychological Aspects